PENGARUH PEMBERIAN ANTIBIOTIK, GLUCOMANNAN HYDROLYSATES (GMH) DAN BALANCE ACTIVE TERHADAP JUMLAH SEL Th2 PADA BACTERIAL VAGINOSIS WANITA USIA SUBUR - Novi Budi; Noorhamdani Noorhamdani; Sri Poeranto (Lembaga Penelitian dan Pengabdian Masyarakat Universitas dr. Soebandi, 2020)
Bacterial Vaginosis is expressed as a polymicrobial infection caused by a decrease in the number of Lactobacillus and is followed by an increase in excessive anaerobic bacteria. Some studies report a cure for bacterial vaginosis of 71-89% or more in women within 1 month after therapy with antibiotics. But with the resistance to antibiotics, some researchers use prebiotics as a treatment for bacterial vaginosis. Glucomannan Hydrolysates (GMH) extracted (as polysaccharides) from Konjac plants that are widely used in Asia as a food source, these prebiotic materials have been tested both in vitro and in vivo and have been shown to be successful with increased growth of lactobacilli or bifidobacteria and reduced pathogens. Besides GMH Active Balance is also used as a regulator of pH.